2014
DOI: 10.3111/13696998.2014.933110
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of add-on treatments to metformin in a Swedish setting: liraglutide vs sulphonylurea or sitagplitin

Abstract: Treatment strategies with liraglutide 1.2 mg improved the expected quality-of-life and increased costs when compared to SU and to sitagliptin for second-line add-on treatments. The cost per QALY for liraglutide was in the range considered medium by Swedish authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…The validation indicated that the model has a predictive accuracy in line with other models of T2D. This model is applicable to CEAs of diabetes in Sweden as it is based on Swedish risks, healthcare system, and costs [27][28][29] .…”
Section: Paɵents Inadequately Controlled On Meƞormin Paɵents Inadequamentioning
confidence: 56%
See 1 more Smart Citation
“…The validation indicated that the model has a predictive accuracy in line with other models of T2D. This model is applicable to CEAs of diabetes in Sweden as it is based on Swedish risks, healthcare system, and costs [27][28][29] .…”
Section: Paɵents Inadequately Controlled On Meƞormin Paɵents Inadequamentioning
confidence: 56%
“…These CEAs were conducted using the IHE Diabetes Cohort Model 26 , which has been used in other CEAs in Sweden [27][28][29] . Briefly, this model uses cohort simulation to estimate the cost-effectiveness of competing interventions for T2D.…”
Section: Methodsmentioning
confidence: 99%
“…The external validation of the model was tested by simulating 12 clinical trials (both interventional and non-interventional) and comparing 167 predicted microvascular, macrovascular and mortality outcomes with those observed in the actual trials [24]. Moreover, the model has been used for several analyses, both in health economic publications [40, 45] and in the development of new national diabetes guidelines [6]. …”
Section: Discussionmentioning
confidence: 99%
“…heart failure, stroke, etc.) were identified from a published Swedish cost-effectiveness analysis (Table S1 in the ESM) [40] and adjusted for inflation to 2013 monetary values. The analysis also included indirect costs of diabetes-related complications.…”
Section: Methodsmentioning
confidence: 99%
“…34 The results were not conclusive for the a GLP-1. 20,21,23,25,33, Albiglutide appeared to be a more cost-effective option than sitagliptin, 35 but the results were the opposite when comparing the general subgroups to which these NIADs belonged (aGLP-1 versus iDPP-4). 20 Exenatide was a more cost-effective treatment than another analogue such as lixisenatide (ICER of €12,600/QALY), 36 but no conclusive results were obtained in comparison with other analogues such as liraglutide, [36][37][38][39][40][41] or dulaglutide.…”
Section: Quality Of the Studiesmentioning
confidence: 97%